Selecting the best AOP for isoxazolyl penicillins degradation as a function of water characteristics: Effects of pH, chemical nature of additives and pollutant concentration (2017)
ABSTRACT: To provide new insights toward the selection of the most suitable AOP for isoxazolyl penicillins elimination, the degradation of dicloxacillin, a isoxazolyl penicillin model, was studied using different advanced oxidation processes (AOPs): ultrasound (US), photo-Fenton (UV/H2O2/Fe2þ) and TiO2 photo- catalysis (UV/TiO2). Although all processes achieved total removal of the antibiotic and antimicrobial activity, and increased the biodegradability level of the solutions, significant differences concerning the mineralization extend, the pH of the solution, the pollutant concentration and the chemical nature of additives were found. UV/TiO2 reached almost complete mineralization; while ~10% mineralization was obtained for UV/H2O2/Fe2þ and practically zero for US. Effect of initial pH, mineral natural water and the presence of organic (glucose, 2-propanol and oxalic acid) were then investigated. UV/H2O2/Fe2þ and US processes were improved in acidic media, while natural pH favored UV/TiO2 system. According to both the nature of the added organic compound and the process, inhibition, no effect or enhancement of the degradation rate was observed. The degradation in natural mineral water showed contrasting results according to the antibiotic concentration: US process was enhanced at low concentration of dicloxacillin followed by detrimental effects at high substrate concentrations. A contrary effect was observed during photo-Fenton, while UV/TiO2 was inhibited in all of cases. Finally, a schema illustrating the enhancement or inhibiting effects of water matrix is proposed as a tool for selecting the best process for isoxazolyl penicillins degradation.